2014
DOI: 10.1021/jp503056u
|View full text |Cite
|
Sign up to set email alerts
|

Following Molecules through Reactive Networks: Surface Catalyzed Decomposition of Methanol on Pd(111), Pt(111), and Ni(111)

Abstract: We present a model of the surface kinetics of the dehydrogenation reaction of methanol on the Pd(111), Pt(111), and Ni(111) metal surfaces. The mechanism consists of 10 reversible dehydrogenation reactions that lead to the final products of CO and H2. The rate coefficients for each step are calculated using ab initio transition state theory that employs a new approach to obtain the symmetry factors. The potential energies and frequencies of the reagents and transition states are computed using plane wave DFT w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
48
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(52 citation statements)
references
References 51 publications
4
48
0
Order By: Relevance
“…A recent study43 on Pt(111) surface shows that it prefers to bind at the bridge position with binding energy -3.39 eV. However, study on cluster surface shows that *CHOH is stable at the top position with adsorption energy of -3.79 eV which is in close agreement with our calculated adsorption energy (-3.67 eV) of *CHOH at the top edge position 18 .…”
supporting
confidence: 90%
See 1 more Smart Citation
“…A recent study43 on Pt(111) surface shows that it prefers to bind at the bridge position with binding energy -3.39 eV. However, study on cluster surface shows that *CHOH is stable at the top position with adsorption energy of -3.79 eV which is in close agreement with our calculated adsorption energy (-3.67 eV) of *CHOH at the top edge position 18 .…”
supporting
confidence: 90%
“…Elongation of C-O bond occurs from 1.22 Å to 1.29 Å, suggesting the change of hybridisation on the carbon centre. Surprisingly, *CHO intermediate calculated to be most stable at the edge position by 0.08 eV than the bridge position though the adsorption energy is higher at the bridge position.Previously Kramer et al43 reported that formyl binds most preferably through C-atom at the top site of the Pt(111) surfaces, with adsorption energy of -2.29 eV whereasDesai et al 19 reported that formyl prefers to adsorb in a di-sigma manner with the adsorption energy -2.45 eV. Gomes et al45 found that formyl adsorbed at the bridge site through C-atom with binding energy of -2.61 eV.…”
mentioning
confidence: 99%
“…Notice that the direct barrier of H 3 COH* dehydrogenation shown Figure 1 is about 91 kJ/mol. In comparison, the barrier was found to range from 39 to 75 kJ/mol in a few early studies [16,37,38]. The difference, due to various factors such as the use of different functionals, surface slab model and transition state search methods, is quite substantial, but is also seen in similar cases.…”
Section: Methodsmentioning
confidence: 97%
“…Also based on DFT calculations, Krajčí et al demonstrated the CO/CO 2 selectivity of MSR on many alloys, e.g., PdZn, PtZn and NiZn [13]. Chen et al [14], Lausche et al [15], and Kramer et al [16] studied the selectivity of the dehydrogenation of methanol on Cu(110), Ni(100) and Ni(111), respectively. MSRs on Pt [16], Pd [16], Pt 3 Ni alloy [17], Pt-Skinned PtNi Bimetallic Clusters [18] and Co [19] have also been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…3d) with the adsorption energy of 0.333 eV ( Table 2). This adsorption mode was generally accepted as the stable configuration [57,58], in which the carbon located on top of Pt atom and the oxygen situated over adjacent Pt atom. The closed-shell electronic configuration of CH 2 O resulted in a weak interaction with PtPd 3 (111) [27,59].…”
Section: Formaldehyde (Ch 2 O)mentioning
confidence: 99%